TECHNIQUE TO RECONSTRUCT BAND 6 REFLECTANCE INFORMATION OF AQUA MODIS - Andy Indradjad; Noriandini Dewi Salyasari; Rahmat Arief (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2016)
Remote sensing data could experience damage due to sensor failure or atmospheric condition. Reconstruction technique to retrieve the missing information had been widely developed in the past few years. This writing aimed to provide a technique to recover reflectance information of Aqua Moderate Resolution Imaging Spectroradiometer (MODIS) Band 6. Since Band 6 Aqua MODIS experienced sensor failure, lots of information would be missing. There were three kinds of methods used in repairing such damage. Two of which were categorized as spatial-based methods, i.e. NaN interpolation method and tensor completion method. Whereas, another method was a spectral-based one. NaN was an interpolation method to reconstruct missing value; while tensor completion method utilized low rank approximation, and spectral method used correlation between Band 6 and Band 7 which had near wavelength. Implementation of these methods was resulted in reconstruction of Aqua Modis Band 6 data which was damaged due to detector disfunction on Aqua Satellite. Peak Signal to Noise Ratio (PSNR) value of this method was 41 dB, meaning that reconstruction technique provided positive impacts for data improvement.